2009
DOI: 10.1097/wad.0b013e31819cb8a2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Preserved Medial Temporal Lobe Volume in Alzheimer Disease

Abstract: Exercise and cardiorespiratory (CR) fitness may moderate age-related regional brain changes in nondemented older adults (ND). The relationship of fitness to Alzheimer's disease (AD) related brain change is understudied, particularly in the hippocampus which is disproportionately affected in early AD. The role of apolipoprotein E4 (apoE4) genotype in modulating this relationship is also unknown. Nondemented (n=56) and early-stage AD subjects (n=61) over age 65 had MRI and CR fitness assessments. Voxel-based mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
137
3
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 65 publications
9
137
3
8
Order By: Relevance
“…Honea et al. (2009) reported positive associations between right parahippocampal volume and CRF in early‐stage AD participants. A two‐year follow‐up study by this same group reported significant associations between CRF change and left parahippocampal volume in the same early‐stage AD participants (Vidoni et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Honea et al. (2009) reported positive associations between right parahippocampal volume and CRF in early‐stage AD participants. A two‐year follow‐up study by this same group reported significant associations between CRF change and left parahippocampal volume in the same early‐stage AD participants (Vidoni et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A two‐year follow‐up study by this same group reported significant associations between CRF change and left parahippocampal volume in the same early‐stage AD participants (Vidoni et al., 2012). Interestingly, neither baseline CRF nor change in CRF was related to hippocampal volume in the cognitively healthy participants of either study (Honea et al., 2009; Vidoni et al., 2012). More recently, change in CRF following an exercise intervention has been positively associated with hippocampal head volume (Maass et al., 2015) and hippocampal tissue density (Kleemeyer et al., 2015) in cognitively healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colcombe et al showed that both gray and white matter increased in healthy older adults as a function of fitness level, but the same correlation was not seen in younger subjects (34). Also, cardiorespiratory fitness was shown to be positively correlated with medial temporal cortex volume in AD patients, but not in healthy controls, suggesting that cardiorespiratory fitness may modify AD-related brain atrophy (75). Most of the studies on fitness and cognition look at leisure time activities, but one study showed that work-related physical activity alone was not protective against dementia or AD later in life (141).…”
Section: Figmentioning
confidence: 99%
“…Physical activity that targets cardiovascular fitness (peak VO 2 ) may offer neuroprotective benefits and attenuate the neuronal structural and functional changes that are associated with MCI and dementia [15][16][17]. Evidence from animal models has demonstrated that aerobic exercise can increase neurogenesis, angiogenesis, learning, and memory in rats [18,19] and inhibit the progression of Alzheimer's-related neuropathology in mice [20].…”
Section: Introductionmentioning
confidence: 99%